2022
DOI: 10.1155/2022/6935609
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Pregnancy-Related Anxiety among Women Attending Antenatal Checkup at Public Health Institutions in Debre Markos Town, Ethiopia

Abstract: Background. Pregnancy-related anxiety has been associated with many pregnancy adverse outcomes including preterm birth, low birth weight, postpartum depression, and resulting in long-term sequels on the child’s emotional, cognitive, and behavioral development. This study is aimed at assessing the magnitude of pregnancy-related anxiety and associated factors among pregnant women attending antenatal checkup at Debre Markos town public health institutions, Northwest Ethiopia. Methods. An institution-based cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
2
1
0
Order By: Relevance
“…This study found that poor social support was associated with maternal depressive symptoms in late pregnancy. This is similar to previous findings that poor social support is significantly associated with anxiety in pregnant women ( 52 ). Moreover, poor social support can lead to a lack of information, tools, and emotional sources, and can make pregnant women feel isolated and lonely, which can predispose them to depressive symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…This study found that poor social support was associated with maternal depressive symptoms in late pregnancy. This is similar to previous findings that poor social support is significantly associated with anxiety in pregnant women ( 52 ). Moreover, poor social support can lead to a lack of information, tools, and emotional sources, and can make pregnant women feel isolated and lonely, which can predispose them to depressive symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…There are only few studies measuring prevalence of anxiety during pandemic. The prevalence in our study was almost double than pre-pandemic, 42%, but it was similar to an Ethiopian and a Poland study (59) (60).…”
supporting
confidence: 86%
“…Our study indicated that anxiety disorders are common during pregnancy and that prevalence rates of anxiety disorders during pregnancy vary considerably between various studies. Prevalence rates of anxiety during pregnancy were reported in six studies (22)(23)(24)(25)(26)(27) and ranged from 10.4% in Qatar (22) to as high as 70.3% in Lebanon (26). This wide variation in prevalence of anxiety during pregnancy may reflect the impact of other additional factors beside pregnancy.…”
Section: Prevalence Of Pregnancy-related Anxietymentioning
confidence: 99%